INTEGRATING THE PREMACK PRINCIPLE AND HENRI NOUWEN’S SPIRITUALITY: A CONCEPTUAL FRAMEWORK FOR ADOLESCENT PASTORAL COUNSELING - Witono Witono; Juliana Hindradjat (MAHABBAH: Journal of Religion and Education, 2026)
Psychological wounds among adolescents in church contexts often manifest in emotional dysregulation, relational difficulties, and disrupted spiritual development. While pastoral counseling has traditionally emphasized relational presence and spiritual formation, such approaches frequently rely on adolescents’ intrinsic motivation, which may be fragile during periods of psychological distress. Conversely, behavioral strategies that support habit formation are often viewed with caution in pastoral settings due to concerns about reductionism and theological incompatibility. Using a qualitative conceptual research design, this study employs a narrative literature review and conceptual thematic analysis to explore the theoretical feasibility of integrating the Premack Principle, a behavioral reinforcement strategy, with Henri Nouwen’s contemplative–relational spirituality within adolescent pastoral counseling. Drawing on interdisciplinary literature in behavioral psychology, pastoral theology, and spiritual formation, the synthesis suggests that while significant paradigmatic tensions exist between external reinforcement and grace-oriented spirituality, these approaches also demonstrate points of conceptual convergence. On this basis, the article proposes a preliminary integrative framework that reframes behavioral reinforcement as temporary scaffolding embedded within pastoral presence and spiritual formation. Rather than claiming empirical effectiveness, the study offers a propositional conceptual foundation to inform theological reflection, pastoral practice, and future empirical research in adolescent pastoral counseling.